Resilience Analysis of Additive Manufacturing-enabled Supply Chains: An Exploratory Study - Patel, Pinkesh; Defersha, Fantahun; Yang, Sheng (Frontiers in Manufacturing Technology, 2022)
Unparalleled level of globalization and fierce competition have made the supply chains exceedingly complex and fragile as ever before. Increased incidences of natural disasters and unprecedented COVID-19 have highlighted the significance of improving supply chain resilience (SCR) by divulging its susceptibility to the external events. Additive manufacturing (AM) is envisioned as the disruptive technology that allows layer-wised fabrication, has been claimed to be an important contributor to the improved SCR as it could bring new opportunities through expanded design freedom, improved material efficiency, shortened supply chains (SC), and decentralized manufacturing. Nonetheless, rare research has quantitatively measured the impacts of AM on SCR. To fill this research gap, the indices for assessing SCR of AM-enabled supply chains (AM-SC) are first proposed, and then the Technique for Order of Preference by Similarity to Ideal Solution (TOPSIS) is employed to derive quantifiable SCR score that can be used to measure the performance of different SCs. A case study of a gas pedal assembly is presented with three different SC configurations – original assembly with conventional manufacturing, original assembly with AM, and redesigned assembly with AM. The exploratory study shows that redesigned assembly with AM considerations could improve the SCR by 200%. Sensitivity analysis also reveals that part count and reaction time of suppliers are influential factors of improving SCR. Lastly, challenges and limitations of the proposed framework are also deliberated upon alongside future research scope.